Innovation, human capabilities, and democracy: Towards an enabling welfare state - Eizagirre Eizagirre, Andoni (Revista Española de Investigaciones Sociológicas, 2024)
Innovation, human capabilities, and democracy: Towards an enabling welfare state Reijo Miettinen Oxford University Press, 2013